Cannabinoids and triple-negative breast cancer treatment - Dobovišek, Luka; Borštnar, Simona; Debeljak, Nataša; Kranjc Brezar, Simona (Frontiers in Immunology, 2024)
Triple-negative breast cancer (TNBC) accounts for about 10-20% of all breast cancer cases and is associated with an unfavorable prognosis. Until recently, treatment options for TNBC were limited to chemotherapy. A new successful systemic treatment is immunotherapy with immune checkpoint inhibitors, but new tumor-specific biomarkers are needed to improve patient outcomes. Cannabinoids show anti-tumor activity in most preclinical studies in TNBC models and do not appear to have adverse effects on chemotherapy. Clinical data are needed to evaluate efficacy and safety in humans. Importantly, the endocannabinoid system is linked to the immune system and immunosuppression. Therefore, cannabinoid receptors could be a potential biomarker for immune checkpoint inhibitor therapy or a novel mechanism to reverse resistance to immunotherapy. In this article, we provide an overview of the currently available information on how cannabinoids may influence standard therapy in TNBC.Triple-negative breast cancer (TNBC) accounts for about 10-20% of all breast cancer cases and is associated with the worst prognosis. TNBC is a heterogeneous group of tumors defined by the absence of the estrogen receptor (ER), the progesterone receptor (PR), and the absence of the human epidermal